Computerization of the Treasury at the Ministry of Finance of Azerbaijan - (:unkn) unknown (My University, 2025)
Ce projet a pour objectif d'analyser le processus de automatisation/numérisation au Ministère des finances de l'Azerbaïdjan.
Keywords: numérisation; automatisation